2014
DOI: 10.1080/02699931.2014.919899
|View full text |Cite
|
Sign up to set email alerts
|

Only your eyes tell me what you like: Exploring the liking effect induced by other's gaze

Abstract: Our preferences are sensitive to social influences. For instance, we like more the objects that are looked-at by others than non-looked-at objects. Here, we explored this liking effect, using a modified paradigm of attention cueing by gaze. First, we investigated if the liking effect induced by gaze relied on motoric representations of the target object by testing if the liking effect could be observed for non-manipulable (alphanumeric characters) as well as for manipulable items (common tools). We found a sig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 32 publications
0
21
0
Order By: Relevance
“…Bayliss et al, 2006), we chose to use a cuetarget asynchrony of 500 ms. The paradigm was also validated in a previous behavioral study of our group (Ulloa et al, 2014). Based on previous EEG and fMRI evidence, we expected to find early modulation of brain responses to targets within occipital and parietal regions following attention orienting by eye gaze.…”
Section: Introductionmentioning
confidence: 91%
“…Bayliss et al, 2006), we chose to use a cuetarget asynchrony of 500 ms. The paradigm was also validated in a previous behavioral study of our group (Ulloa et al, 2014). Based on previous EEG and fMRI evidence, we expected to find early modulation of brain responses to targets within occipital and parietal regions following attention orienting by eye gaze.…”
Section: Introductionmentioning
confidence: 91%
“…Thus, people may be more susceptible to mimicry of a person who is in agreement with them because more of their perception and attention is directed toward that person's behavior than a person who is in disagreement with them. People are more likely to gaze at faces that are similar to themselves (Hungr & Hunt, 2012) and gaze at people and objects they like (Schotter, 2010;Ulloa, Marchetti, Taffou, & George, 2015); however, future research may want to examine the moderating role of attention more directly, possibly by measuring participants' eye gaze toward each confederate to establish that participants are directing more of their attention toward the confederate in agreement with them. For example, research has found that pictures of emotional content received more participant eye gazes and for longer durations than neutral content, and even more so if the emotional content was pleasant rather than nonpleasant (Nummenmaa, Hyönä, & Calvo, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, the significant findings for the gaze-liking effect range from dz = 0.35 (Ulloa, Marchetti, Taffou, & George, 2015) to 1.22 (for trustworthy faces; King et al, 2011). Moreover, some studies have reported non-significant results in conditions that were expected to show an effect: 1) for gaze cues on ratings for garage objects (Ulloa et al, 2015) and 2) for pointing gestures on ratings for kitchen and garage and other objects (Ulloa et al, 2015). Overall, there is considerable variability in the reported effect sizes and research would benefit from a more precise estimate of the effect size.…”
Section: Replication To Quantify the Size Of The Gaze Liking Effect Imentioning
confidence: 99%
“…This is challenging because as stated above, previous studies have reported varying effect sizes. Our solution was to base our sample size on being able to detect the smallest significant effect size reported in the literature; dz = 0.35 (Ulloa et al, 2015) with a specific level of precision: We wanted our most likely estimates to fall within a region no larger than dz = .5 (plus or minus dz = 0.25). Although the study by Ulloa et al was not a direct replication of the original study (it included a different set of faces and additional conditions) the sample size was larger (N=36) than in the original study, making it a reasonable candidate for the smallest effect size of interest.…”
Section: Sample Size Justificationmentioning
confidence: 99%